(untitled) (New Delhi, 2004)
A varied cross section of India’s current intelligentsia contribute to this anthology of essays addressing what India represents for today and what it should stand for in the future. Aside from its booming economy there are a number of key issues India must confront, among them the treatment of women and minorities, the conflict between secularism and religion, and cultural phenomenons like the rise of Bollywood. Just as significant as the pragmatic aspects of these concerns is the degree to which they affect India’s overall image—the idea of India—both internally and internationally.
Keywords: India,Ấn Độ; History,Lịch sử; 1947 -,1947 -